The functionalism in Peruvian criminal law: appreciations, theories and practice - Villa Stein, Javier (2009)
In the recent years, systemic or normative functionalism has been set up and spread out in the Peruvian Criminal Law scholar doctrine and case law, in a clear, precise and coherent manner providing solutions to concrete problems which were previously left behind to be answered by the naturalist, ontologist and teleologist scholar doctrines. Thus, by having an advanced functionalism approach, we explain the previous evolution and stand assumed by the great master of Bonn, Günther Jakobs, who sets out the functional relation between society and the criminal-juridical dogmatics, which must be re-based with a view to safeguard the social and state system through the maintenance of the criminal law stability to guarantee the citizen’s minimum expectations regarding proper functioning of social life.